The Significance of Photography as Archives and Cultural Memory - Criscentia Jessica Setiadi (Humaniora, 2017)
This research was conducted by using textual, qualitative approach while looking closer at the significant of the information that was produced in the form of photography. The aim of this research was to take a stance of the importance of photography as archives and cultural memory in its ability in promoting truths. Photography was observed as three forms; they were singular, plural, and archival. Singular forms suggested the selective association between the photographers and the photographs were taken. Plural formed resonance ideas and overall aspects in what sets of photography could bring. Archival forms offered memories as references. The result of this research shows that photography, despite its ability or inability in promoting truths, is a great pool of resources of gaining information and tracing history. Further to this research, looking closer to current social media applications that put photography forward can be one option to explore within this topic.